PENYULUHAN TENTANG DEMAM TIFOID DI SMA NEGERI 01 KOTABUMI LAMPUNG UTARA - Djunizar Djamaludin; Setiawati Setiawati (Universitas Malahayati Lampung, 2018)
ABSTRACTTyphoid fever is a bacterial infection in humans caused by salmonella thypi disorder characterized by prolonged fever, abdominal pain, diarrhea, delirium, splenomegaly, and sometimes accompanied by complications of bleeding and bowel perforation. This bacterial spread through various way with 5 F: Food, Fingers, Vomitus, Flies and Feces. The predisposition of this disease is to buy their own food or snacks for daily consumption and usually occurs through consumption of food outside the home or in public places, if food or drinks are less clean. The purpose of this activity is expected it is expected that students be able to understand the importance of preventing the incidence of typhoid fever through a healthy lifestyle. This activity was carried out on Saturday, May, 28th, 2018 with a total of 32 students. Activities carried out with counseling method of the students about typhoid fever in Public Senior High School 01 Kotabumi, North Lampung by using LCD projector and leaflet. There was a significant effect on students’ knowledge before and after counseling. As a result of this counseling found that by providing education be able to improved knowledge, particularly relating to typhoid fever.Keywords: Typhoid fever, Level of Knowledge, Counseling